Seguimiento de la cooperación sur-sur: presentación - Surasky, Javier (Revista Española de Desarrollo y Cooperación, 2023)
In this occasion the South-South Cooperation Monitoring Commission is focused on two important events that took place in the second half of 2009: The starting up of the South-South Cooperation Task Team in both Regional meetings in Latin America and Caribbean area; and the Latin America-Africa Summit, where it was signed the South Bank Constitutive Agreement.